Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

AriPotta

  • 3 years ago

check to see if this is right please? put in general form: y = x^2 + 14x + 29 y = x^2 + 14x + 29 y - 29 = x^2 + 14x y - 29 = x^2 + 14x + 49 y + 20 = (x + 7)^2 y = (x + 7)^2 - 20

  • This Question is Closed
  1. pooja195
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    y = x² + 14x + 29 y-29=x²+14x y-29+49=(x+7)² y=(x+7)² - 20

  2. pooja195
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    CORRRRRCET!!!! :)

  3. AriPotta
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    thanks :]

  4. pooja195
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    np!

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy